Survival of very preterm infants: Epipage, a population based cohort study. Issue 2 (1st March 2004) - Larroque, B; Bréart, G; Kaminski, M; Dehan, M; André, M; Burguet, A; Grandjean, H; Ledésert, B; Lévêque, C; Maillard, F; Matis, J; Rozé, J C; et al.
Abstract : Objective: To evaluate the outcome for all infants born before 33 weeks gestation until discharge from hospital. Design: A prospective observational population based study. Setting: Nine regions of France in 1997. Patients: All births or late terminations of pregnancy for fetal or maternal reasons between 22 and 32 weeks gestation. Main outcome measure: Life status: stillbirth, live birth, death in delivery room, death in intensive care, decision to limit intensive care, survival to discharge. Results: A total of 722 late terminations, 772 stillbirths, and 2901 live births were recorded. The incidence of very preterm births was 1.3 per 100 live births and stillbirths. The survival rate for births between 22 and 32 weeks was 67% of all births (including stillbirths), 85% of live births, and 89% of infants admitted to neonatal intensive care units. Survival increased with gestational age: 31% of all infants born alive at 24 weeks survived to discharge, 78% at 28 weeks, and 97% at 32 weeks. Survival among live births was lower for small for gestational age infants, multiple births, and boys. Overall, 50% of deaths after birth followed decisions to withhold or withdraw intensive care: 66% of deaths in the delivery room, decreasing with increasing gestational age; 44% of deaths in the neonatal intensive care unit, with little variation with gestational age. Conclusion: Among very preterm babies, chances of survival varies greatly according to the length of gestation. At all gestational ages, a large proportion of deaths are associated with a decision to limit intensive care.